Microwave Assisted Synthesis of Biocompatible Silver Nanoparticles Using Ficus carica Fruit Extract - Logaranjan, K.; P, K. (Asian Journal of Chemistry, 2013)
The influence of Ficus carica fruit extracts on formation of silver nanoparticles under various experiment conditions in both conventional heating and microwave heating were studied. The shape and size of the silver nanoparticles depending upon the heating rate, pH of the medium and concentration of Ficus carica fruit extract. An enhanced antimicrobial activity was noted for biomolecules stabilized silver nanoparticles.